Diversity of phytoplankton collected during the scientific expedition to Pulau Perak, Pulau Jarak and the Sembilan Group of Islands - Salleh, Aishah; Ahmad Wakid, Sarini; Shah Bahnan, Iskandar (Malaysian Journal of Science, 2008)
Preliminary studies on the phytoplankton in the Straits of Malacca were conducted during the ‘Scientific Expedition to the Seas Of Malaysia’ (SESMA). Phytoplankton samples were collected from Pulau Perak, Pulau Jarak and the Sembilan group of Islands. The quantitative analysis was carried out especially on the identification and calculation of the diversity of the phytoplankton. A total of 69 species of phytoplankton from 17 genera were recorded. The species were mainly from two major divisions namely Bacillariophyta (diatoms) and Pyrrophyta (dinoflagellates). Five species are new records for Malaysia: Peridinium quinquecorne Abé, Protoperidinium cerasus (Paulsen) Balech, Protoperidinium nudum (Meunier) Balech, Ceratium arietinum Cleve and Ceratium compressum Gran.